PERSONALISASI MATEMATIS DALAM E-LEARNING MELALUI LEARNING MANAGEMENT SYSTEM - Euis Setiawati (Balai Diklat Keagamaan Bandung, 2018)
The rapid development of science and technology has not fully brought a new paradigm in learning mathematics, seen by a large number of internet users only limited to the use of social media in every circle. The purpose of writing this scientific paper is to describe elearning as a way of learning built by the Learning Management System (LMS), and how this system can play a role in personalizing mathematical concepts. The research method used is descriptive analysis by collecting data, compiling or classifying, analyzing, and interpreting several types of software commonly used in e-learning. The results of the analysis show that mathematical personalization can occur by utilizing the features contained in the topics of LMS and is very useful for building learning objects that are suitable to overcome various didactic obstacles in mathematics learning, encourage more semiotic coordination in presentations, and avoid bad classroom practices during mathematics learning. Personalization through LMS can also produce different didactic abilities by considering the profiles of students. Key words: personalization, mathematics, e-learning, learning management system.